Homes by design rethinking apartment. Ep. 610 - Jeans, Katherine; Hobin, Barry J.; Sound Venture Production; Fashion Television Channel (Firm) (New York : Sound Venture Productions, 2007)
Program that shows in designing apartment into more exclusive places
Title from title screen
Originally broadcast as an episode of the television program Homes by design
DVD Format
Keywords: Architecture, Domestic; Buildings -- Remodeling for other use; Interior decoration